Investing in professionalized maintenance to increase social and economic returns from drinking water infrastructure in rural Kenya - Foster, T; Hope, R; Koehler, J; Katuva, J; Thomson, P; Gladstone, N (University of Oxford, 2022)
Repairing rural water infrastructure quickly through professionalized maintenance can reduce costs and increase social and economic returns, with benefits for low income households and women. This policy brief examines the case of water supply infrastructure in rural Kenya, and finds the case for investment in improved maintenance becomes compelling when factoring in wider social and economic returns, though will require major institutional change and accountable coordination between government, donors, and NGOs. Key findings: -When rural water infrastructure is not professionally maintained, household spending on alternative water sources due to breakdowns in supply can be as much as the initial capital costs of the infrastructure -Professionalized maintenance can reduce repair times to less than two days for both piped systems (otherwise, 46–67 days) and handpumps (otherwise, 43 days) -Drought events increase socio-economic hardship, particularly for handpump users with only a few days of water storage -For handpump users, the cost of alternative sources in the dry season increases by up to USD 0.38 per day, equivalent to 6–14% of daily household expenditure -Women bear the vast majority of time costs of collecting water from alternative sources -Governments and donors can pay three times more per litre of water from emergency water trucking compared to the cost of water provided by a functioning kiosk